PENGARUH MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN PELATIHPUSAT PEMBINAAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) KOTA PADANG TENTANG AVULSI GIGI - Satria Yandi; Intan batura endo mahata; widya puspita sari; Mitha ari cahaya putri (Universitas Baiturrahmah, 2022)
Introduction: Student Sports Training and Development Center (PPLP) is a forum for prospective athletes to develop their sports talents without neglecting their achievements in the academic field. Sports activities are one of the activities that are at risk of dental avulsion. Knowledge of dental avulsion was very important for a trainer. The purpose of this study was to determine the effect of audio- visual media on the knowledge of the West Sumatra PPLP trainers about tooth avulsion. Method: This research is quantitative pre- experimental research with one group pretest-posttest design. A total of 24 samples were used and measurements were made using a questionnaire. Results: The average knowledge of respondents before the intervention was 10.79 with a standard deviation of 2.340, the lowest knowledge score was 6 and the highest knowledge score was 14, the average knowledge of respondents after the intervention was 13.42 with a standard deviation of 1.585, the lowest knowledge score was 8 and the highest knowledge score is 15. Conclusion: There is an effect of audio-visual media as an educational medium on the level of knowledge of the Padang City PPLP trainers about the occurrence of dental avulsions.